Study of Risk Factor for Congenital Heart Diseases in Children at Rural Hospital of Central India - Taksande, Amar M; Vilhekar, Krishna (Journal of Nepal Paediatric Society, 2013)
Introduction: Congenital heart disease is the most common congenital problem that accounts for up to 25% of all congenital malformations. Hence this study was aimed at improving the knowledge related to risk factors associated with CHD in a rural Indian scenario. It was a hospital- based case control study. Materials and Methods: The children up to twelve year of age with clinical suspicion of CHD were subjected to chest x-ray and electrocardiography, and final diagnosis was confirmed by echocardiography (n=209) as cases. The control group (n=418) were randomly selected from children without CHD who were admitted during the same period. The etiological factors like environmental, infections, drugs, and maternal factors were analyzed by using EPI 6 version. Results: In cases group, 56% were male and 44% female children. 82% cases presented at age of less than 5 years and 18% after 5 year. Exposure to smoking (OR=10.45), tobacco intake by mother (OR=8.28) and family history of CHD (OR=7.21) were the significant risk factor present in cases. Conclusion: The risk factors for CHD child identified were exposure to smoking and tobacco intake by mother, family history of CHD, antenatal infection in 1st trimester and history of diabetic mother. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8254 J Nepal Paediatr Soc. 2013; 33(2):121-124